2007
DOI: 10.1029/2006ja011845
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal and vertical propagation and dissipation of gravity waves in the thermosphere from lower atmospheric and thermospheric sources

Abstract: [1] The dissipation of high-frequency gravity waves (GWs) in the thermosphere is primarily due to kinematic viscosity and thermal diffusivity. Recently, an anelastic GW dispersion relation was derived which includes the damping effects of kinematic viscosity and thermal diffusivity in the thermosphere and which is valid before and during dissipation. Using a ray trace model which incorporates this new dispersion relation, we explore many GW properties that result from this dispersion relation for a wide range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
650
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 352 publications
(699 citation statements)
references
References 58 publications
(129 reference statements)
48
650
1
Order By: Relevance
“…Here, the indices i, j =1, 2, 3 indicate the components of the vector quantities x, V , k, and c g , and repeated indices imply a summation. The subscript "r" here denotes the real component of the frequency (Vadas andFritts, 2005, hereafter VF2005), not the relative frequency; the relative frequency (i.e., the frequency in the intrinsic frame of reference moving with the fluid) is denoted by the subscript "I ", where "I " stands for "intrinsic" (see Table 1 for definitions). We do not allow the ground-based frequency of a GW to vary in time in our model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the indices i, j =1, 2, 3 indicate the components of the vector quantities x, V , k, and c g , and repeated indices imply a summation. The subscript "r" here denotes the real component of the frequency (Vadas andFritts, 2005, hereafter VF2005), not the relative frequency; the relative frequency (i.e., the frequency in the intrinsic frame of reference moving with the fluid) is denoted by the subscript "I ", where "I " stands for "intrinsic" (see Table 1 for definitions). We do not allow the ground-based frequency of a GW to vary in time in our model.…”
Section: Methodsmentioning
confidence: 99%
“…16 were also used to infer GW amplitudes at higher altitudes in the TI for this SpreadFEx campaign Fritts et al, 2008b). GWs with λ z > ∼ 100 km are those we expect to penetrate to the greatest altitudes, based on the viscous dispersion relation developed by VF2005 and the ray tracing studies by Vadas (2007) and Fritts and Vadas (2008). Fritts et al (2008b) employed the results of this study to infer maximum horizontal velocities near z∼80 km of ∼1−2 ms −1 for GWs with λ z ∼150 km and λ H ∼200−400 km arising from a single convective plume, with amplitudes ∼2 times larger in response to a small convective cluster.…”
Section: Spectral Amplitudes At Airglow Altitudesmentioning
confidence: 99%
“…Note that θ=90 o if the wave is propagating eastward. Although GWs with horizontal wavelengths greater than 100 km can penetrate above the turbopause, they must typically have intrinsic phase speeds greater than c I H >100 m/s to propagate to the bottomside of the F-region (Vadas, 2007). Using Eq.…”
Section: Medium-scale Gravity Waves In the Oh Airglow Layermentioning
confidence: 99%
“…Since kinematic viscosity and thermal diffusivity increase nearly exponentially with altitude, eventually every GW dissipates, although at differing altitudes depending on its characteristics (Vadas and Fritts, 2006;Vadas, 2007). As a GW begins to dissipate, its momentum flux decreases less rapidly with altitude.…”
Section: Forward Ray Tracing Medium-scale Gravity Wavesmentioning
confidence: 99%
“…Singh et al (1989) from a detailed analysis of the data reported that TIDs were detected at distances more than 500 km away from the umbra region. Theoretical estimates show that the period and amplitude of gravity waves is dependent on the bearing of the source with respect to the observing point in the ionosphere (Chimonas, 1970;Vadas, 2007). First experimental signatures of the existence of gravity waves were observed with periodicity of 30-33 min in ionosphere.…”
Section: Introductionmentioning
confidence: 99%